Less conservative conditions for stabilization of switched TS fuzzy systems using fuzzy Lyapunov functions - Faria, Flavio A. [UNESP]; Oliveira, Vilma A.; Elias, Leandro J.; Capela, Jorge M. V. [UNESP]; Tanaka, Julia S. [UNESP]; IEEE (Ieee, 2018)
Relaxed conditions to stabilize switched TS fuzzy systems are proposed. The method considers the addition of slack matrix variables to decrease the conservatism of LMI-based stability conditions. The proposed method is an extension of recent published results. Numerical examples illustrate its efficiency.
Keywords: Switched TS fuzzy systems; Fuzzy Lyapunov functions; Linear matrix inequalities (LMIs)